Refractive Changes Induced by Strabismus Corrective Surgery in Adults - Daphna Mezad-Koursh; Ari Leshno; Tomer Ziv-Baran; Chaim Stolovitch (Journal of Ophthalmology)
Purpose. To investigate refractive changes after strabismus correction procedures among adults. Methods. Retrospective chart review of adult patients who had horizontal recti muscles surgery with preoperative and postoperative cycloplegic refraction measurements. The preoperative refraction was mathematically subtracted from the postoperative refraction, and the induced refractive changes were statistically analyzed. Vector analysis was used to examine the magnitude of the toric change. The proportion of clinically significant refractive change was evaluated as well. Results. Thirty-one eyes from 22 subjects met the criteria and were included in the final analysis. A significant postoperative refractive change of the spherical equivalent towards myopia and a change of the astigmatism in the with-the-rule direction were observed. In a subset of 9 cases a third cycloplegic refraction measurement demonstrated stable refraction compared to the 1-month postoperative measurement. In 10 cases of single eye surgery, significant refractive changes were observed only in the operated side when compared to the sound eye. The induced surgical refractive change was of clinical significance (≥0.5 D) in 11 eyes of 9 patients (40.9% of patients). Conclusions. Refractive changes are a significant side effect of horizontal strabismus corrective surgery among adults. Therefore, patients should be informed about it prior to surgery and should be rerefracted in the postoperative period.